HCAL-J: hadron calorimeter for the study of nucleon form factors at Jefferson Lab. Issue 9 (3rd October 2018) - Brio, V.; Bellini, V.; Petta, C.; Re, L.; Sutera, C. M.; Tortorici, F.; Wojtsekhowski, B.; Cornejo, J. C.; Franklin, G.; Quinn, B.
ABSTRACT: HCAL-J is a hadron calorimeter under construction at JLAB in Newport News, VA (USA). The main interest of the JLAB physics is the study of the hadron matter properties, using a longitudinally polarised electron beam; in particular, researchers investigate the electromagnetic form factors of nuclei and nucleons using the Continuous Electron Beam Accelerator Facility (CEBAF) accelerator, which provides a beam of 12 GeV electrons. The upgrade to higher energies allows measurements at high values of Q 2 and a more in-depth study of the internal structure of the hadron matter. To this purpose, Hall A collaboration is building the SuperBigBite Spectrometer (SBS), which consists of a series of elements including a dipole magnet to curve the trajectory of the recoil particles, and a series of Gas Electron Multiplier (GEM) to track the particles. Moreover, two analyzers for the measurement of the polarisation components and a hadron calorimeter, HCAL-J, to measure the particle energy, are used in order to apply the so-called recoil polarisation method, which consists in measuring both the longitudinal and transverse polarisation of the scattered nucleon. The study, through SBS, of the electromagnetic form factors of nucleons allows obtaining the ratio between these two components, which results to be proportional to the ratio between the electric and magnetic form factors of the nucleon. HCAL-J is a sampling calorimeter useful to measure the energy of the recoil nucleon; its active area consists of 288 modules that include a matrix with 24 modules in height and 12 in width. There are optical fibres in between each module, connected to a photomultiplier, in order to look at the light from the scintillating material and convert it into an electric signal, related to the energy of the incident particle.